2022
DOI: 10.1039/d2sd00042c
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two cortisol aptamers for label-free fluorescent and colorimetric biosensors

Abstract: Cortisol is a stress hormone and the abnormal secretion of cortisol is related to many chronical diseases and neurological disorders. To detect cortisol, two DNA aptamers have been reported so...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
4
16
0
Order By: Relevance
“…The original CSS.1 with a 6 bp stem generated the largest fluorescence difference with a K d of 1.1 μM. This K d value was very close to the K d measured by ITC (0.7 μM), 16 verifying that PMNT showed very little interference on aptamer binding.…”
Section: ■ Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…The original CSS.1 with a 6 bp stem generated the largest fluorescence difference with a K d of 1.1 μM. This K d value was very close to the K d measured by ITC (0.7 μM), 16 verifying that PMNT showed very little interference on aptamer binding.…”
Section: ■ Introductionsupporting
confidence: 76%
“…14,15 The conformational change of aptamers after target binding can either promote dye binding or displace dye molecules, resulting in a fluorescence intensity change. 16,17 However, these label-free biosensors show relatively low fluorescence change due to the noncanonical structures of aptamers. Strategies using terminal-labeled fluorophore and quencher pairs to form aptamer beacons were also employed.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cortisol aptamer (CSS.1) reported by the Stojanovic group was used ( Figure A), [ 51 ] and we previously reported that cortisol does not have strong interactions with AuNPs. [ 52 ] The optimal concentration of aptamer was determined to be 500 n m (Figure S8, Supporting Information), where the slope started to plateau and the solution color turned blue. In addition, a nonbinding mutant (CSS.1‐mt) was also used.…”
Section: Resultsmentioning
confidence: 99%